Change in choroidal thickness after intravitreal aflibercept in pretreated and treatment-naive eyes for neovascular age-related macular degeneration - Mazaraki, Kyriaki; Fassnacht-Riederle, Heidi; Blum, Robert; Becker, Matthias D.; Michels, Stephan (British journal of ophthalmology, 2015)
Aim Evaluation of effects of intravitreal aflibercept therapy on choroidal thickness (CT) in neovascular age-related macular degeneration. - Methods Retrospective cohort study evaluating the change in CT following a loading dose of three intravitreal aflibercept injections at 4 weeks interval. Pretreated and treatment-naive eyes as well as untreated fellow eyes were evaluated at five retinal locations (subfoveal, 300 and 2500 µm nasal and temporal to the fovea) using spectral domain optical coherence tomography prior to and 4 weeks after a loading dose of three intravitreal aflibercept injections. - Results A total of 84 treated eyes (61 pretreated, 23 treatment naive) and 48 fellow eyes were enrolled into the study. Treatment-naive and pretreated eyes showed a significant reduction in CT at all retinal locations. The effect was more pronounced in treatment-naive eyes. In the pretreated group, the mean reduction in CT was greatest at 2500 µm temporal to the fovea at 10.7 µm compared with 22.4 at 300 µm nasal to the fovea in the treatment-naive group. Only the fellow eyes in the treatment-naive group showed a significant CT reduction 12 weeks after initiation of therapy to the partner eye. - Conclusions Aflibercept induces a reduction in CT in treatment-naive and pretreated eyes with neovascular age-related macular degeneration. There is some evidence of a systemic effect of aflibercept reflected by CT reduction in untreated fellow eyes.